Constraints Faced by Rural Youth for Opting Entrepreneurship as Career: A Case Study of Haryana - Kiran,; Pathania, Ankit; Vikash,; Meena, Satyveer Singh (Indian Journal of Extension Education, 2025)
The study was carried out to examine the constraints faced by rural youth for starting their own venturesduring 2023. Multi-stage sampling was used for data collection. The data were collected from 396 respondents from three districts of Haryana through a well-structured questionnaire. The relationship of gender was checked with the eight statements of social factors. The data were analysed using Weighted Average Mean (WAM) and constraint faced by rural youth were ranked accordingly. The constraints were categorised in five categories i.e. personal, social, market, financial and government support and subsidy. The major constraints faced by the rural youth were caste biasness, underestimation of individual ability by society, delayed payment of bills, inadequate savings, non-availability of skilled/trained manpower and complexity in availing schemes/ subsidies from the government agencies. The relation of gender was found significant with two statements, i.e. lack of family support and limited mobility.
Keywords: Constraints; Entrepreneurship; Rural youth; Venture